Wetting Defects: Simultaneous Detection and Repair of Wetting Defects in Superhydrophobic Coatings via Cassie–Wenzel Transitions of Liquid Marbles (Adv. Funct. Mater. 26/2019). (25th June 2019) - Tenjimbayashi, Mizuki; Samitsu, Sadaki; Naito, Masanobu
Abstract : Damage of superhydrophobic coatings is inevitable despite improvements in mechanical durability and/or self‐healing. In article number1900688, Mizuki Tenjimbayashi, Masanobu Naito, and Sadaki Samitsu demonstrate a system of simultaneous detection and repair of damaged surface areas using the wetting transition phenomenon of liquid marbles. In this system, the liquid marble recovers the surface wettability in response to wetting defects, which enables sustainable material interfaces.